Biomass Burning Smoke and Its Influence on Clouds Over the Western U. S. Issue 15 (2nd August 2021) - Twohy, Cynthia H.; Toohey, Darin W.; Levin, Ezra J. T.; DeMott, Paul J.; Rainwater, Bryan; Garofalo, Lauren A.; Pothier, Matson A.; Farmer, Delphine K.; Kreidenweis, Sonia M.; Pokhrel, Rudra P.; Murphy, Shane M.; Reeves, J. Michael; et al.
Abstract: Small cumulus clouds over the western United States were measured via airborne instruments during the wildfire season in summer of 2018. Statistics of the sampled clouds are presented and compared to smoke aerosol properties. Cloud droplet concentrations were enhanced in regions impacted by biomass burning smoke, at times exceeding 3, 000 cm −3 . Images and elemental composition of individual smoke particles and cloud droplet residuals are presented and show that most are dominantly organic, internally mixed with some inorganic elements. Despite their high organic content and relatively low hygroscopicity, on average about half of smoke aerosol particles >80 nm diameter formed cloud droplets. This reduced cloud droplet size in small, smoke‐impacted clouds. A number of complex and competing climatic impacts may result from wide‐spread reductions in cloud droplet size due to wildfires prevalent across the region during summer months. Plain Language Summary: Wildfires over the western United States produce large quantities of smoke during the summer months. The smoke includes airborne particles that can act as nuclei for forming individual droplets in clouds. Particles and clouds in the region were sampled with a research aircraft to measure the properties of smoke particles and how they influenced the properties of small cumulus clouds. Clouds were strongly influenced by smoke across the western U.S. On average, sampled clouds had about 5x as many droplets, and droplets were about 1/2 the size, as in clouds not influenced by smoke. Because of their small droplet sizes, these smoky clouds are expected to reflect more light and produce less rain than clouds in clean air. Other complex effects are possible due to warming impacts of the smoke itself, and due to other potential impacts of smoke aerosols on larger, deeper clouds. Key Points: Western wildfires produce organic particles that readily act as cloud condensation nuclei due to their large size and partial hygroscopicity Wildfire smoke strongly impacts the microphysics of small cumulus clouds, which have high droplet concentrations and small droplet sizes Diverse impacts on radiative forcing and precipitation are possible over the western U.S. and downwind due to wildfire smoke